Too Sweet to Ignore: How SSB Intake and Physical Inactivity Affect BMI in Malang’s Student Population - Rahmawati, Indana Tri; Ulfah, Nurnaningsih Herya; Renawati, Anggi; Gunawan, Yuvica Novita (citeus, 2025)
The growing incidence of overweight and obesity in young adults has been closely associated with unhealthy lifestyle habits, particularly the high intake of sugar-sweetened beverages (SSBs) and low levels of physical activity. College students are especially at risk due to lifestyle changes that occur during their university experience. This research aims to investigate the SSB consumption patterns, physical activity levels, and their correlation with Body Mass Index (BMI) among university students in Malang City. A descriptive cross-sectional study was carried out with 382 active students chosen through accidental sampling. Data were obtained using an online questionnaire shared through student networks and social media platforms. The results indicated that 73.8% of participants expressed a preference for SSBs, with bottled tea being the most commonly consumed, primarily bought from minimarkets. While 63.4 percent of students reported exercising 1 until 2 times a week, 68.1 percent participated in low-intensity activities, and 43.7 percent worked out for less than 30 minutes. A strong correlation was identified between SSB consumption and BMI (p is 0.882, 2-tailed), while physical activity showed a weak and non-significant association (p is 0.128). The need for targeted health promotion programs aimed at reducing SSB intake and encouraging students to engage in more efficient physical activity routines is highlighted by these results.